Differential miRNA expression in human macrophage-like cells infected with histoplasma capsulatum yeasts cultured in planktonic and biofilm forms - Pitangui, Nayla de Souza [UNESP]; Singulani, Junya de Lacorte [UNESP]; Sardi, Janaina de Cássia Orlandi; de Souza, Paula Carolina [UNESP]; Rodríguez-Arellanes, Gabriela; García-Pérez, Blanca Estela; Enguita, Francisco Javier; Pavan, Fernando R. [UNESP]; Taylor, Maria Lucia; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (MDPI, 2021)
Histoplasma capsulatum affects healthy and immunocompromised individuals, sometimes causing a severe disease. This fungus has two morphotypes, the mycelial (infective) and the yeast (parasitic) phases. MicroRNAs (miRNAs) are small RNAs involved in the regulation of several cellular processes, and their differential expression has been associated with many disease states. To investigate miRNA expression in host cells during H. capsulatum infection, we studied the changes in the miRNA profiles of differentiated human macrophages infected with yeasts from two fungal strains with different virulence, EH-315 (high virulence) and 60I (low virulence) grown in planktonic cultures, and EH-315 grown in biofilm form. MiRNA profiles were evaluated by means of reverse transcription-quantitative polymerase chain reaction using a commercial human miRNome panel. The target genes of the differentially expressed miRNAs and their corresponding signaling pathways were predicted using bioinformatics analyses. Here, we confirmed biofilm structures were present in the EH-315 culture whose conditions facilitated producing insoluble exopolysaccharide and intracellular polysaccharides. In infected macrophages, bioinformatics analyses revealed especially increased (hsa-miR-99b-3p) or decreased (hsa-miR-342-3p) miRNAs expression levels in response to infection with biofilms or both growth forms of H. capsulatum yeasts, respectively. The results of miRNAs suggested that infection by H. capsulatum can affect important biological pathways of the host cell, targeting two genes: one encoding a protein that is important in the cortical cytoskeleton; the other, a protein involved in the formation of stress granules. Expressed miRNAs in the host’s response could be proposed as new therapeutic and/or diagnostic tools for histoplasmosis.
Keywords: Biofilms; Fungal-host interactions; Histoplasma capsulatum; Macrophages; MicroRNAs